ANTI-INFLAMMATORY, ANTI-NOCICEPTIVE AND ANTIPYRETIC POTENTIAL OF TERMINALIA CITRINA FRUIT EXTRACTS - Saleem, Ammara; Javeed, Aqeel; Ashraf, Muhammad; Akhtar, Muhammad Furqan; Akhtar, Bushra; Sharif, Ali; Akhtar, Kanwal; Raza, Moosa; Hamid, Irfan; Peerzada, Sohaib; Ahmad, Shoaib; Atta, Sania (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: Plants and herbs have long been used as remedies without scientific evidences. The objective of the present study was to explore the anti-inflammatory, anti-nociceptive and antipyretic potential of ethanolic and aqueous extracts of Terminalia citrina fruits in mice. Materials and Methods: Extracts of Terminalia citrina fruits were evaluated at doses of 200mg/kg, 400mg/kg and 600mg/kg in albino mice for preventive effect in inflammatory edema, peripheral pain sensation and pyrexia. Carrageenan induced paw edema method was utilized to evaluate anti-inflammatory activity. Analgesic appraisal of extracts was demonstrated using acetic acid induced writhing model of pain. Antipyretic potential was determined by brewer’s yeast induced pyrexia model. Statistical analysis was conducted by ANOVA following post hoc test. Results: Both extracts exhibited significant and dose-dependent anti-inflammatory, analgesic and antipyretic activities. The ethanolic extract was more effective in reducing inflammatory edema, pyrexia and pain sensation than aqueous extracts in all tested doses. Conclusion: It can be concluded that fruit extracts of Terminalia citrina may be effective in reducing inflammation, pyrexia and pain sensation in animals.